Genetic divergence in buckwheat (Fagopyrum esculentum) - JOSHI, B D; RANA, J C (The Indian Journal of Agricultural Sciences, 2013)
Forty genotypes of buckwheat (Fagopyrum esculentum Moench) from different parts of India were grouped into 12 clusters. Intra-cluster D2 values were 0-11.07 and inter-cluster 14.40-48.36. Cluster VII ranked first for seed yield/plant (25.06 g), branches/plant (6.80) and leaf length (6.37 cm). Genetic diversity and geographical distribution were not related. ’IC 37312’ originating from Sikkim was most divergent among all the genotypes. The 4 canonical vectors accounted for 97.57% of the total genetic variation. Plant height contributed maximum (36.94%) toward divergence. ’IC 13375’, ’Kulu Gangri’, ’Himpriya’, ’IC 16654’, ’IC 37275’, ’IC 107992’ and’IC 17312’ were found promising genotypes for buckwheat improvement.